ANALYSIS OF TECHNOLOGY USE IN ENGLISH LANGUAGE LEARNING: TEACHER AND STUDENT PERSPECTIVES - MOHAMMAD NURWAHID (Journal of Language, Literature and Teaching, 2026)
This study aims to analyze the use of technology in English learning at Baitul Hikmah Islamic Junior High School from the perspective of teachers and two students in grade VII-F. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The results indicate that technologies such as Duolingo and interactive media improve students' motivation and language skills. Teachers consider technology effective but need to be balanced to prevent reducing critical thinking skills. The main obstacles are internet connection and limited devices. Suggestions include improving infrastructure, teacher training, and implementing a blended learning model.